Haben : the deafblind woman who conquered Harvard Law - Girma, Haben, 1988- (Twelve, 2019)
Documents the story of the first deaf and blind graduate of Harvard Law School, tracing her refugee parents' harrowing experiences in the Eritrea-Ethiopian war and her development of innovations that enabled her remarkable achievements.